LGBT COMMUNITY ACTIVITIES IN RUSSIA AFTER THE EXTENSION OF THE LGBT PROPAGANDA LAW 2022 - Aysiwi, Sabrina Rafika; Yumitro, Gonda (Moestopo Journal of International Relations (MJIR), 2025)
Russia is widely recognized for its opposition to the LGBT movement, particularly through the implementation of the 2013 Gay Propaganda Law, which was further expanded by President Vladimir Putin in 2022. This extension has significantly intensified restrictions on the activities of the LGBT community within the country. This study aims to analyze the social impact of the 2022 extension of the Gay Propaganda Law, both in public life and in digital spaces. The findings were obtained using qualitative methods, including content analysis of credible Russian news sources and a literature review of peer-reviewed academic journals published between 2015 and 2025. The results indicate that the extension of the law has had a substantial negative impact on the LGBT community, leading to increased marginalization, a heightened sense of threat due to legal constraints, and limited opportunities for expression, both on social media and in broader society. This study contributes to a deeper understanding of the consequences of anti-LGBT legislation and may serve as a reference for future research on social and political developments related to LGBT issues in Russia